Multilingualism in content and language integrated learning (CLIL) classroom contexts: Commentary on the special issue - Morton, Tom (Learning and instruction, 2025)
Content and Language Integrated Learning (CLIL) is a growing research area, yet tensions persist between monolingual ideologies and multilingual classroom realities. This Special Issue addresses these tensions by exploring CLIL through diverse epistemological lenses, with translanguaging as a central theme. This commentary critically engages with the Special Issue, organizing cross-cutting themes using Pennycook’s (2024) concept of “practical assemblage.” It examines how the studies conceptualize multilingualism in CLIL as a language matter of concern, how translanguaging functions as a practical theory of language, and how ethical and critical issues emerge in restrictive language policy contexts. The Special Issue includes eight studies spanning diverse global contexts, from EMI settings to bilingual and immersion programmes, highlighting CLIL’s role as an umbrella term and its evolving, context-dependent nature. The commentary synthesizes insights from the studies, categorizing them into three dimensions: (a) conceptualizing CLIL and its terminological plurality, (b) translanguaging and multimodality in knowledge construction, and (c) critical perspectives on linguistic justice and equity. The findings demonstrate how activating learners’ multilingual and multimodal repertoires through translanguaging facilitates epistemic access. However, while CLIL is increasingly framed as multilingual and multimodal, monolingual ideologies persist, especially in contexts with restrictive language policies. This Special Issue shifts CLIL towards a dynamic, multilingual assemblage rather than a rigid content-language model. Future research should further integrate translanguaging, multimodality, and critical perspectives to ensure CLIL fosters rather than restricts linguistic diversity. •CLIL is seen as a multilingual phenomenon, challenging monolingual views.•Translanguaging in CLIL activates multilingual and multimodal repertoires.•Multimodality is key to meaning-making in CLIL classrooms.•Persistent monolingual ideologies may limit CLIL's potential.•Inclusive translanguaging practices are needed to ensure social justice in CLIL.